The Difficulties and Countermeasures of the Development of Universal Benefit Private Kindergartens - Zhang, Xin; Shen, Yuran (Journal of Theory and Practice in Education and Innovation, 2024)
Preschool education is the beginning of lifelong education, and nurturing from infancy is the common expectation of the people. Comrade made it clear in the report of the 19th CPC National Congress that "preschool education should be done well and that every child can enjoy a fair and quality education." In recent years, China has carried out the action plan of preschool education in an all-round way, and made a breakthrough in the cause of preschool education. However, with the acceleration of urbanization and the implementation of the comprehensive two-child policy, the imbalance between the demand for preschool education and the development and supply of preschool education is still very prominent. The development of the universal benefit private kindergartens has become an important practical way to "basically build a public service system for preschool education that covers a wide range of areas, ensures basic and quality education". However, in the process of developing the universal benefit private kindergartens, there are a series of difficult problems such as vague identification standards, general support policies, weak faculty and inadequate regulatory mechanisms. Therefore, it is necessary to scientifically define the connotation of the universal private kindergartens, improve the training system of preschool teachers, accelerate the construction of its internal education quality assurance system, and constantly improve the long-term policy support and supervision mechanism, so as to make them play an important role in expanding public preschool education resources and promoting education and social equity.